Peningkatan Kualitas Pelayanan Administrasi - Wibawa, Samodr; Purbokusumo, Yuyun (Magister Administrasi Publik (MAP) FISIPOL Universitas Gadjah Mada, 1998)
This article is supposed to offer a constructive ideas for creating better public bureaucracy at the operational level. It assumed that Indonesian political system is beginning to be more opened as the political will among the decision makers are ready to create clean governance. A crucial question is to be answered: How to improve administrative service? Given the fact that different appeciation on ideal type of bureaucracy would imply different idealized quality of service, it is imperative to understand what should be the ideal typr of public bureaucracy. From an exploratory discussion about an ideal type bureaucracy and its services in Indonesia and Germany, the writers pointed out that quality improvement can only be accomplished if public bureaucracy eager to transform ots orientation to the costumers. Public bureaucracy should acknowledge that community and customers deserve to get the best quality of service. Involving the costumers to evaluate the output and measuring the achievement of public bureaucracy is a simple yet an excellent way of improving quality of services.